Serli Discovery Learning Dalam Mendukung Pembelajaran Ilmu Pengetahuan Alam Siswa Berbasis Android: Serli Discovery Learning in Supporting Android-Based Natural Science Learning for Students - Putri Febrina, Annisa; Ngemba, Hajra Rasmita; Hendra, Syaiful; Anshori, Yusuf; Azizah, Azizah (Technomedia Journal, 2024)
The development of information technology, have a positive impact on education by providing flexible learning support. The design and presentation of the learning tool significantly affect students' interest in learning. In the current technological era, students and teachers must consider the accessibility and mobility of learning media. The purpose of this research is to develop the SERLI Application, an android-based Natural Science learning module that can be accessed anywhere by students and teachers. The application development model used is the Hannafin & Peck Model, which consists of  needs analysis,  design  stages, and  implementation & development. The method for evaluating user satisfaction uses the End User Computing Satisfaction method. This method considers variables such as content, accuracy, display format, ease of use, and timeliness. The experts tested the SERLI Application, gave a 86.58% success rate. Student users and teachers also evaluated the application and achieved a 85% success rate. These results are very good. The implementation result of this research is an android-based learning application product that contains a science lesson module. In this application, there is an initial display, namely registration into the application, then the main display of the application which contains modules and practice questions, then the display for the teacher.